Voltage Sensor Inactivation in Potassium Channels - Bähring, Robert; Barghaan, Jan; Westermeier, Regina; Wollberg, Jessica (Frontiers in Pharmacology, 2012)
In voltage-gated potassium (Kv) channels membrane depolarization causes movement of a voltage sensor domain. This conformational change of the protein is transmitted to the pore domain and eventually leads to pore opening. However, the voltage sensor domain may interact with two distinct gates in the pore domain: the activation gate (A-gate), involving the cytoplasmic S6 bundle crossing, and the pore gate (P-gate), located externally in the selectivity filter. How the voltage sensor moves and how tightly it interacts with these two gates on its way to adopt a relaxed conformation when the membrane is depolarized may critically determine the mode of Kv channel inactivation. In certain Kv channels, voltage sensor movement leads to a tight interaction with the P-gate, which may cause conformational changes that render the selectivity filter non-conductive (“P/C-type inactivation”). Other Kv channels may preferably undergo inactivation from pre-open closed states during voltage sensor movement, because the voltage sensor temporarily uncouples from the A-gate. For this behavior, known as “preferential” closed-state inactivation (CSI), we introduce the term “A/C-type inactivation”. Mechanistically, P/C- and A/C-type inactivation represent two forms of “voltage sensor inactivation”.